2018
DOI: 10.2106/jbjs.17.00883
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Ankle Osteoarthritis Is Related to Increased Ankle Pain and a Worse Clinical Outcome Following Total Knee Arthroplasty

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 19 publications
5
48
0
Order By: Relevance
“…In a study by Takeuchi, the treatment of varus knee malalignment via closing-wedge high tibial osteotomy significantly reduced ankle pain and improved its function [20]. However, Chang et al reported that the presence of ankle OA was associated with increased ankle pain and a worse clinical outcome after TKA, presumably due to the reduced valgus compensation of the hindfoot for the preoperative varus tilt of the ankle [7]. In the present study, hindfoot alignment after TKA was found to be 4 of valgus in case 1 and 25 of valgus in case 2, where the normal alignment of the hindfoot could be restored manually by passive stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Takeuchi, the treatment of varus knee malalignment via closing-wedge high tibial osteotomy significantly reduced ankle pain and improved its function [20]. However, Chang et al reported that the presence of ankle OA was associated with increased ankle pain and a worse clinical outcome after TKA, presumably due to the reduced valgus compensation of the hindfoot for the preoperative varus tilt of the ankle [7]. In the present study, hindfoot alignment after TKA was found to be 4 of valgus in case 1 and 25 of valgus in case 2, where the normal alignment of the hindfoot could be restored manually by passive stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that the greater the tilt of the ankle is, the more degenerative the changes are in the knee joint [6]. In addition, the incidence of ankle OA in patients with end-stage knee OA before total knee arthroplasty (TKA) is reported to be 24.2%e36.8% among ethnic Asian populations [5,7]. In a previous prospective multicenter cohort study, the presence of foot/ankle symptoms in people with symptomatic radiographic knee OA was proven to be associated with an increased risk of knee pain aggravation [8].…”
Section: Introductionmentioning
confidence: 99%
“…The eligible studies included a total of 913 patients x, MTA or the angle formed between the mechanical axis of the femur and the mechanical axis of the tibia; y, HA or the angle between the diaphyseal axis of the tibia and the longitudinal axis of the calcaneus; z, AOFAS or the American Orthopedic Foot and Ankle Score; {, Tt or the angle between the distal tibial surface and the upper talus; |, MAJS or the distance between the medial of the talar dome and the distal tibial surface; }, MACS or the distance between the medial articular surface of the talus and the medial malleolus articular surface. and 1,157 knees, which included four prospective cohort studies (13,16,17,19) and four retrospective studies (5,14,15,18).…”
Section: Research Detailsmentioning
confidence: 99%
“…However, in clinical scenarios, some patients complain of aggravation of ankle pain after surgery. Some of these patients have preexisting ankle OA [3][4][5][6]. Ankle pain following TKA is very troublesome and is associated with poorer clinical outcomes [3,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these patients have preexisting ankle OA [3][4][5][6]. Ankle pain following TKA is very troublesome and is associated with poorer clinical outcomes [3,5,7]. Therefore, to implement TKA in patients with both knee and ankle problems, one must consider possible postoperative changes in ankle alignment in the context of preventing ankle symptom exacerbation.…”
Section: Introductionmentioning
confidence: 99%